ANALISIS YURIDIS PENGGUNAAN PASAL 338 KUHPIDANA DALAM TINDAK PIDANA PENGANIAYAAN - Fotuhoaro Ndruru; Setiyono (Reformasi Hukum Trisakti, 2023)
Juridically, committing the act of killing another person with intention or negligence is of course an act that violates the rules of criminal law, so that the criminal act of murder can be given criminal sanctions. The problem in this research is to find out the description of the suitability between the actions committed by the perpetrator and the elements of criminal acts in Article 338 of the Criminal Code, and what is the description of the suitability of the sentence imposed using the provisions of Article 338 of the Criminal Code. Normative legal research using descriptive secondary data which is then processed using qualitative analysis with deductive logic to draw conclusions, is the research method used in this writing. The results of the research and discussion were that the judge had declared the defendant guilty of committing the crime of murder and sentenced to 15 years in prison. In conclusion, the actions carried out by the defendant complied with the provisions contained in Article 338 of the Criminal Code and the sentence imposed by the panel of judges was in accordance with the provisions of Article 338 of the Criminal Code.